Molecularly toxicological and immunological responses of Nile tilapia (Oreochromis Niloticus, Linnaeus) to sil ver nanoparticle induction - Kubpaphas Thummabancha (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Nile tilapia thioredoxin-interacting protein (On-TXNIP) and selenoprotein P (On- SEPP) cDNAs were cloned and characterized. The full-length cDNA of On-TXNIP cDNA was 2,260 bp and consisted of 116 bp of 5' untranslated region (UTR), 1,188 bp of open reading frame (ORF) (equal to 396 amino acid residues), 925 bp of 3'UTR and 28 bp of a poly A tail. The calculated theoretical isoelectric point (pI) and molecular weight (MW) of On-TXNIP were 7.81 and 43.95 kDa, respectively. The full-length cDNA of On-SEPP was 2,427 bp and consisted of 99 bp of 5'UTR, 1,239 bp of ORF (equal to 413 amino acid residues), 1,086 bp of 3'UTR, and 29 bp of a poly A tail. The calculated pI and MW of On-SEPP were 6.27 and 46.36 kDa, respectively. Evolutionary analyses of both the On-TXNIP and On-SEPP genes revealed that these genes were closely related to the TXNIP and SEPP genes in zebrafish (Danio rerio). A normal tissue distribution analysis indicated that the On-TXNIP and On-SEPP genes were ubiquitously expressed in all tissues examined, and the highest expression levels of these genes were observed in peripheral blood leukocytes (PBLs) and the trunk kidney, respectively. The expression analysis of cellular stress response genes using real-time reverse transcription polymerase chain reaction (real-time RT PCR) in fish acutely and chronically exposed to 1, 10 and 100 mg Ag NPs/kg fish by intraperitoneal (i.p.) injection revealed that significant up- regulation of On-TXNIP and On-SEPP transcripts was in the liver, spleen, and head kidney at the early phase of Ag NP exposure (hours 6 through 48). Down-regulation of On-SEPP transcripts was clearly observed in the liver at weeks 1 to 4. The statistically up-regulated On- HSP40B9, On-HSP90α and On-HSP90β transcripts were observed in all tested tissues of fish exposed to Ag NPs at hours 6 and 12 and down-regulated On-HSP70 and On-MT genes were found in the liver at hours 6 to 48. Histopathological analysis demonstrated that the fish livers exhibited a dramatic infiltration of Kupffer cells, elevated bi-nucleated cells, expanded sinusoidal blood congestion and severe necrosis in a dose-dependent manner. Thickening of the capsule layer of the spleen was a predominant indicator of chronic Ag NP exposure under i.p. induction. Innate and adaptive immunological responses and hematological parameters of fish exposed to various doses of Ag NPs revealed that phagocytic activity, amounts of red blood cells (RBCs) and the percentage of hematocrit (%Hct) significantly decreased at week 1 after exposure. However, amounts of white blood cells (WBCs) were not significantly changed at all-time exposure (P>0.05). Additionally, antibody titer of fish immunized with Streptococcus agalactiae vaccine and simultaneously exposed to Ag NPs at 10 and 100 mg/kg were found to effectively decrease at only early phase. Finally, in the challenge test, all vaccinated fish with Ag NPs-exposed groups were still protected against S. agalactiae infection. Based on these findings, the expression analysis of cellular stress response genes, histopathological observation, and compromising of innate immune response of fish exposed to Ag NPs could be reliable for the assessment of Ag NP contamination in teleost fish.